2022
DOI: 10.3390/nano12071115
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Green Synthesis of Ag NPs for Extenuating Antimicrobial Resistance

Abstract: Combating antimicrobial resistance (AMR) is an on-going global grand challenge, as recognized by several UN Sustainable Development Goals. Silver nanoparticles (Ag NPs) are well-known for their efficacy against antimicrobial resistance, and a plethora of green synthetic methodologies now exist in the literature. Herein, this review evaluates recent advances in biological approaches for Ag NPs, and their antimicrobial potential of Ag NPs with mechanisms of action are explored deeply. Moreover, short and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 149 publications
2
12
0
Order By: Relevance
“…TEM images of silver nanoparticles have shown that the morphology of silver nanoparticles was predominantly quasi-spherical with a mean diameter of 12.3 nm and a standard deviation 2.56 nm. These results are similar to those obtained by other authors using the same methodology [51][52][53] . This is due to the bioreduction from various compounds in the medium, as commonly occurs in green synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…TEM images of silver nanoparticles have shown that the morphology of silver nanoparticles was predominantly quasi-spherical with a mean diameter of 12.3 nm and a standard deviation 2.56 nm. These results are similar to those obtained by other authors using the same methodology [51][52][53] . This is due to the bioreduction from various compounds in the medium, as commonly occurs in green synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…This results in morphological alterations, including cytoplasmic contraction, cell wall separation, and cell membrane rupture. 57,58 In addition, the zinc and silver ions produced by ZnO-Ag NPs may enter microorganisms, providing the synergistic effect of preventing the multiplication or synthesis of different biological components. 59,60 This suggests that the use of bimetallic MNPs for broad-spectrum antimicrobial applications is benecial.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table 1, 9 goals which are expected to be achieved in the near future are selected as an example. Some powder processes and products considering the SDGs have been reviewed: e.g., food (Bartolucci et al, 2020), pharmaceutical (Assali and Zaid, 2022), agricultural material (Swoboda et al, 2022), catalyst (Nawaz et al, 2021), antibacterial material (Bhardwaj et al, 2021;Parmar et al, 2022), environmental improvement material (Nnadozie and Ajibade, 2020;Rehman et al, 2021). The use of fine particles in the processes shows many merits such as uniformity and reactivity; however, some serious demerits such as safety, labor environment and air pollution are latent.…”
Section: Sdgs In Powder Processingmentioning
confidence: 99%